Scientometric analysis of research on emissions control from 2007 to 2017 (2018)
A scientometric analysis of the production of scientific publications on emissions control from 2007 to 2017 was carried out. HistCite was used to analyze information collected from Web of Science (WoS) on this topic during this period. The results suggest that scientific publications in this field have steadily increased over the years during the last decade. China is the country with the highest number of publications, and the Chinese Academy of Sciences represents the institution with the highest number of publications. Most of the papers and citations came from developed countries. The top three journals with highest number of papers in this field are Applied Physics Letter, Atmospheric Environment, and Environmental Science & Technology.